Updates on Evidence-Based Practices to Reduce Preoperative and Intraoperative Contamination of Implants in Spine Surgery: A Narrative Review - Aakash Agarwal; Boren Lin; Hossein Elgafy; Vijay Goel; Chris Karas; Christian Schultz; Neel Anand; Steve Garfin; Jeffrey Wang; Anand Agarwal (Spine Surgery and Related Research, 2020)
The current communication seeks to provide an updated narrative review on latest methods of reducing implant contaminations used during spine surgery. Recent literature review has shown that both preoperative reprocessing and intraoperative handling of implants seem to contaminate implants. In brief, during preoperative phase, the implants undergo repeated bulk cleaning with dirty instruments from the OR, leading to residue buildup at the interfaces and possibly on the surfaces too. This, due to its concealed nature, remains unnoticed by the SPD (sterile processing department) or other hospital staff. Nevertheless, these can be avoided by using individually prepackaged presterilized implants. In the intraoperative phase, the implants (in the sterile field) are directly touched by the scrub tech with soiled (assisting the surgeon dispose the tissues from the instruments in use) gloves for loading onto an insertion device. It is then kept exposed on the working table (either separately or next to the used instruments as the pedicles hole are being prepared). Latest investigation has shown that by the time it is implanted in the patient, it can harbor up to 10e7 bacterial colony-forming units. The same implants were devoid of such colony-forming units, when sheathed by an impermeable sterile sheath around the sterile implant.